Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11746-009-1407-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrothermal Treatment of Rapeseed on Antioxidant Capacity of the Pressed Rapeseed Oil

Abstract: Response surface methodology (RSM) was used to evaluate the quantitative effects of two independent variables, rapeseed moisture content and conditioning temperature, on the antioxidant capacity (AC) and total phenolic (TPC), tocopherol (TTC), and phosphorus contents (PC) in the pressed rapeseed oils. The mean AC results for the crude rapeseed oils ranged from 199.8 to 947.2 lmolTE/100 g. TPC and PC in the crude rapeseed oils correlated significantly (P \ 0.01) and positively with AC of oils (R 2 = 0.9498 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Contrary to this result, Lee et al [10] reported an increase in the tocopherol content of safflower oil as the roasting temperature increased from 140 to 180°C. It is also well known that oxidative stability and extraction of tocopherols depend greatly on the processing temperature and the period of time during which the temperature is applied [30]. At the processing conditions used in this study, a highly significant (p B 0.001) decrease in tocopherol content was observed in pumpkin seed oils produced at higher temperature.…”
Section: Tocopherols and Total Polyphenolsmentioning
confidence: 58%
See 1 more Smart Citation
“…Contrary to this result, Lee et al [10] reported an increase in the tocopherol content of safflower oil as the roasting temperature increased from 140 to 180°C. It is also well known that oxidative stability and extraction of tocopherols depend greatly on the processing temperature and the period of time during which the temperature is applied [30]. At the processing conditions used in this study, a highly significant (p B 0.001) decrease in tocopherol content was observed in pumpkin seed oils produced at higher temperature.…”
Section: Tocopherols and Total Polyphenolsmentioning
confidence: 58%
“…To our knowledge, there are no published data about the influence of processing conditions on the phenol content of pumpkin seed oils. In various materials such as Pistacia terebinthus fruit, rapeseed, sesame and peanut, it has been reported that roasting increases the passage of phenolic compounds to oils probably by releasing them from their bonds to various cellular components [11,30,32,33].…”
Section: Tocopherols and Total Polyphenolsmentioning
confidence: 99%
“…Another study suggested that the phytosterol contents in five different breeds of rapeseed were 5964-8197 mg/kg [19]. The quantitative effects of rapeseed moisture content and conditioning temperature on the level of tocopherol in pressed rapeseed oils had been evaluated in the past, and tocopherol contents between 710 and 750 mg/kg were found [26]. It can be generally concluded that the concentrations of tocopherols and phytosterols are influenced by the rapeseed variety, storage conditions, moisture content, and conditioning temperature [19,25,26].…”
Section: Analysis Of Tocopherols and Phytosterolsmentioning
confidence: 99%
“…Canola oil has beneficial health properties as it is low in saturated fats and contains a significant amount of essential fatty acids. On the other hand, this oilseed can also be used as a raw material for the production of alternative fuels (biodiesel) due to its high oil content, high yield per hectare and the good quality of its oil . Presently, solvent extraction is the most commonly used method to recover oil from oilseeds.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this oilseed can also be used as a raw material for the production of alternative fuels (biodiesel) due to its high oil content, high yield per hectare and the good quality of its oil. [1] Presently, solvent extraction is the most commonly used method to recover oil from oilseeds. This process is controlled by mass transfer phenomena involving taking the oil from inside the lipid bodies to the solvent.…”
Section: Introductionmentioning
confidence: 99%